#### Answer

1

#### Work Step by Step

From the table, we see that: $g(2)=5$ and $g(5)=1$, so we have:
$g(g(2))=g(5)=1$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

1

From the table, we see that: $g(2)=5$ and $g(5)=1$, so we have:
$g(g(2))=g(5)=1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.